(untitled) (Bioscience Journal, 2020)
Popillia japonica (Coleoptera: Scarabaeidae), Japanese beetle, is a polyphagous pest of many crops. In these crops, including apple, it acts primarily as a defoliator, causing economic damages. The objectives were to determine the ability of P. japonica to injury fruits of SweeTango variety apples and the suitability of apple fruits as a food source for this beetle. Popillia japonica was not able to injure the surface of intact fruits, which means that it is not a primary pest for apple fruits. The lifespan of the beetles when fed soybean leaves or apple with exposed endocarp was similar. Observations of the feces of the beetles suggest a potential physiological response due the change of food from soybean leaves to apple fruits. Therefore, we can conclude that the adults should not be considered as primary pests of apple fruits; however, they may act as secondary pests if the endocarp of the fruits is exposed by some other agent.